Projetos na pauta de duas revistas pedagógicas (1939-2009) - Moraes, Lenir dos Santos (Universidade do Vale do Rio do Sinos, 2010)
This dissertation aims to examine some ways in which the pedagogical discourses constituted a way of thinking about education through the organization by putting projects under suspicion inside the order of that name and the yield set in motion by practices expressed that way. To carry out my investigations, I used as research material two educational journals: the Journal of Teaching in Rio Grande do Sul and the New School Journal, analyzing the recurrences of the discourses that circulate in these journals. I put into play looks from the perspective that takes language as constitutive of reality, searching for conditions of possibility that gave support to the meanings built to designs in contemporary and examined how this practice have been working in dealing with the conduct to serve as a powerful strategy and tactics for put into action different technologies of power machinery in the government school in this population. In the performed analytical, I argument that the use of the term to indicate projec
Keywords: discursos pedagógicos; tecnologias de poder; práticas de projetos; pedagogic speeches; technologies of power; practices of projects; Ciências Humanas